OPTIMIZATION OF CONCENTRATION AND SOAKING TIME OF HARRIS HEMATOXYLIN IN DNA BAND EXAMINATION USING ELECTROPHORESIS - Fajri, Siti Nuristiqomah; Asep Iin Nur Indra; Fusvita Merdekawati; H. , Acep Tantan (Journal of Vocational Health Studies, 2024)
Background: Deoxyribonucleic acid (DNA) molecules can be effectively visualized when stained and observed under ultraviolet light during the electrophoresis process. The commonly used dye Ethidium bromide (EtBr) is considered hazardous due to its potential to cause mutations, cancer, and congenital disabilities. Various alternative dyes have been reported, one of which is hematoxylin. Hematoxylin compounds do not have mutagenic potential and are easier to apply than EtBr. However, there is no optimal variation in concentration and duration of staining for clear and effective visualization of DNA bands. Purpose: To find the concentration and staining time of harris hematoxylin staining for DNA bands from agarose gel electrophoresis. Method: An experimental method with a group comparison statistical design. The amplified DNA I6S rRNA gene from Escherichia coli (584 bp), which had undergone electrophoresis, was stained using harris hematoxylin dye at 0.01%; 0.02%; 0.03%; 0.04%; and 0.05% concentrations and immersion times soaking times of 10, 15, 20, and 30 minutes variations. The intensity of the DNA bands was analyzed using ImageJ. The staining power of the experimental groups was compared to the intensity of control dye and given a grading score of 1 - 4. The experiment was repeated twice, and the mean grading score was calculated. The highest mean value was considered the most optimal value. Result: A concentration of 0.02% showed relatively constant staining intensity for each soaking time. A mean value of 3.5 was obtained for a 0.01% concentration for 15 minutes. A 0.03% and 0.04% concentrations for 20 minutes. Conclusion: The highest mean value of 4 was obtained for Harris hematoxylin at 0.05% for 15 minutes.